1996
DOI: 10.1055/s-2006-957888
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Cytokine Stimulating Activities of Heteroglycans fromTremella fuciformis

Abstract: Three heteroglycans, T1a, T1b, and T1c, have been isolated from the body of Tremella fuciformis Berk. They are composed of mannose (Man), xylose (Xyl), glucose (Glc), fucose (Fuc), and glucuronic acid (GlcA). According to methylation analysis and partial acidic hydrolysis the main chains of T1a, T1b, and T1c consisted of (1-->3)-linked Man, which was branched at the 2, 4, or 6 positions. The branching points were linked with nonreducing terminal GIcA-residues or (1-->6)-linked glucan-chains. Molecular weights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 4 publications
2
21
0
1
Order By: Relevance
“…XG is derived from Xanthomonas campestris, has a pentasaccharide repeating unit structure, and its terminus contains a mannose moiety which acts as a toll-like receptor 2 agonist. T is extracted from Tremella fuciformis (TreE) and contains non-starch polysaccharide components (b-glucans) that exhibit immunomodulating properties and induce humoral and cellular immune responses [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…XG is derived from Xanthomonas campestris, has a pentasaccharide repeating unit structure, and its terminus contains a mannose moiety which acts as a toll-like receptor 2 agonist. T is extracted from Tremella fuciformis (TreE) and contains non-starch polysaccharide components (b-glucans) that exhibit immunomodulating properties and induce humoral and cellular immune responses [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a low-molecular-weight (20 kDa) fraction from the fruiting body of Agaricus blazei was found to exhibit tumor-specific cytocidal and immunopotentiating effects (Fujimiya, Suzuki, Katakura, & Ebina, 1999). In addition, acidic hydrolysate fractions, with molecular weights ranging from 53 to 1 kDa, from the fruiting body of Tremella fuciformis, induced human monocytes to produce interleukin-6 as efficiently as the non-hydrolyzed fraction (Gao, Jiang, Chen, Jensen, & Seljelid, 1996). It has been shown that a triple-helical tertiary conformation of medicinal mushroom-derived polysaccharide was important for their immune-stimulating activity indicating that polysaccharide-mediated immuno-pharmacological activities were dependent on the helical conformation (Yanaki, Ito, & Tabata, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (2008) demonstrated that chemical str ucture of the polysaccharides consists of a linear backbone of (1→3) α-D-mannan (with side chains composed of glucuronic acid, xylose and fucose) backbone chain to which β-(1→2)-linked D-xylose residues are attached at the C-2 position. The estimated ratio of mannose, fucose, xylose, and glucuronic acid is 9:1:4:3 that makes glucoronic acid accounted for 17.6% of the polysaccharides content in T. fuciformis (De Baets and Vandamme, 2001;Gao et al, 1996Gao et al, , 1997Tsing, 2006;Wu et al, 2008;Kakuta et al, 1979;Khondkar, 2009).…”
Section: Analysis Of Tremella Fuciformismentioning
confidence: 99%